ADAM17 Boosts Cholesterol Efflux and Downstream Effects of High-Density Lipoprotein on Inflammatory Pathways in Macrophages. Issue 6 (22nd April 2021) - Kothari, Vishal; Tang, Jingjing; He, Yi; Kramer, Farah; Kanter, Jenny E.; Bornfeldt, Karin E.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: HDL (high-density lipoprotein) can exert both anti-inflammatory and proinflammatory effects in macrophages due to its ability to induce cholesterol depletion. Because cholesterol depletion also increases sheddase activity of the membrane protease ADAM17 (ADAM metallopeptidase domain 17) in other cells, we examined if ADAM17 plays a role in HDL's effects on inflammatory processes in macrophages in vitro and in vivo. Approach and Results: Sorted peritoneal macrophages from human APOA1 (apolipoprotein A1) transgenic LDL (low-density lipoprotein) receptor-deficient ( APOA1 Tg ; Ldlr −/− ) mice with and without myeloid cell-targeted ADAM17-deficiency were studied in parallel with wildtype and ADAM17-deficient bone marrow-derived macrophages stimulated with HDL in vitro. HDL increased ADAM17 expression and activity in macrophages. Furthermore, ADAM17-deficient macrophages exhibited reduced expression of ABCA1 (ATP-binding cassette A1) and reduced cholesterol efflux and were cholesterol loaded. This was caused by the absence of shedding of TNFα, a major ADAM17 substrate. Sorted thioglycollate-elicited peritoneal macrophages freshly isolated from APOA1 Tg ; Ldlr −/− mice, which have higher HDL levels than Ldlr −/− controls, showed reduced expression of interferon-inducible genes in response to lipopolysaccharide or interferon β, but exacerbated proinflammatory responses to lipopolysaccharide for Tnfa, Cxcl1, Ccl2, and Il1b, phenocopying cells stimulated with HDL in vitro. These effects were all prevented in ADAM17-deficient macrophages and associated with lower concentrations of large HDL particles in APOA1 Tg ; Ldlr −/− mice with myeloid cell-targeted ADAM17-deficiency. Conclusions: The increased cholesterol loading of ADAM17-deficient macrophages prevents both anti-inflammatory and proinflammatory responses of HDL. Our findings demonstrate a novel role for ADAM17 in maintaining cholesterol efflux in macrophages, thereby regulating the immune functions of these cells.